PERBEDAAN PANJANG TEROWONGAN SEGITIGA TERHADAP C/N RASIO KOMPOS SAMPAH ORGANIK DENGAN METODE AEROB DI PT. X (Politeknik Kesehatan Kemenkes Bandung, 2021)
Garbage is inseparable from human life. If the number and activity of the population are increasing, the generation of waste will increase too. PT. X produces organic waste as a form of human activity. Based on the calculation, the average waste generated is 25,6 liter/day. To reduce it, an aerobic method of composting is carried out by providing passive aeration through a triangle tunnel. The purpose of this research was to determine the difference in variation the length of triangle tunnel on the value of C/N ratio. The length of triangle tunnel used in this research were 40 cm, 45 cm, and 50 cm. This research is an experimental research with a post-test with control design. The population in this research were all of organic waste produced by PT. X and the samples in this research were leaf waste and vegetable waste. The results of this research is average value of C/N ratio for the 40 cm triangle tunnel was 20.27; 45 cm 22.34; 50 cm 22.55. According to PERMENTAN 70/2011, the final result of C/N ratio is 15-25. One-Way Anova statistical test shows that there is a difference in the length of triangle tunnel on the value of C/N ratio because P value (0,013) ≤ (0.05). For further research, the moisture content at the end of the composting process must be considered, so the shrinkage of the volume can reach 60%.